Etiological factors of abnormal uterine bleeding according to PALM- COEIN classification in perimenopausal women in a tertiary care centre - Mitra, Nishi; Patil, Pooja; Sethia, Ayushi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Perimenopause is described as years prior to menopause that encompasses the change from normal ovulatory cycle to cessation of menses, ending 12 months after the last menses. International federation of gynaecology and obstetrics (FIGO) developed a new classification PALM-COEIN in order to standardize the factors associated with AUB. It classifies AUB as polyp, adenomyosis, leiomyoma, malignancy and hyperplasia (PALM) - structural abnormalities Coagulopathy, ovulatory dysfunction, endometrial, iatrogenic, not yet classified (COEIN) - unrelated to structural abnormalities. Objectives of this study were to categorise the causes of AUB in perimenopausal women in context to PALM COEIN classification system. Correlation of co-morbities (diabetes, hypertension and thyroid disorders) with AUB in perimenopausal age group. Methods: This is a retrospective study from the month of May 2019 to October 2019, considering 100 patients of perimenopausal age group (40 to 55 years of age group) in J. K. Hospital Bhopal, Madhya Pradesh with complaints of abnormal uterine bleeding, admitted in gynae ward. Results: Most of the patients in the current study were between 45-50 years of age i.e. 44%. Menorrhagia was the commonest menstrual disorder encountered in 52% of patients. As per FIGO; AUB-L constituted 42% AUB-O constituted 12%, AUB-P constituted 11%, AUB-A 10%, AUB-M constituted 8% AUB-E constituted 8%, not yet classified constituted 4% of total cases. Conclusions: AUB (PALM-COEIN) for causes of abnormal uterine bleeding classification was very useful in categorizing cases of AUB. It suggests that etiology of AUB and also gives place for presence of multiple factors as a cause of AUB in a particular case.